Group Counseling Model of Rational Emotive Behavior Based on ASWAJA Values for Increase Moderation Religious Students: Preventive Efforts Counter Radicalism - Fadhilah, Ningsih; A. Tabi’in; Ahmad Minan Zuhri; Muh. Azhar Mubarak (Universitas PGRI Yogyakarta, 2026)
Radicalism among university students shows a worrying trend, especially through the penetration of intolerant ideologies on social media; therefore, a value-based preventive approach is needed. The purpose of this study is to develop a Rational Emotive Behavior Therapy (REBT) group counseling model based on Ahlussunnah wal Jamaah (ASWAJA) values to enhance students’ religious moderation. The research employed a Research and Development (R&D) design following the Borg and Gall model, encompassing preliminary studies, model design, expert validation, and field testing. The expert validation yielded a feasibility score of 130, categorized as good and appropriate. The effectiveness test utilized a pre-test–post-test control group design involving 20 students from Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan selected through purposive sampling. Data were analyzed qualitatively and quantitatively using a paired sample t-test. The results revealed a p-value of 0.000 (p < 0.05) and an N-Gain of 60.09% (moderate), indicating the model’s effectiveness in improving religious moderation. This study presents an innovative counseling model that integrates REBT with ASWAJA values, contributing theoretically to the development of value-based REBT approaches and, practically, as a preventive framework against radicalism in higher education. Keywords: group counseling, REBT, ASWAJA, radicalism, religious moderation